THE DEVELOPMENT OF PREEMINENT ISLAMIC SCHOOL IN INDONESIA - Abd Rahman; Zuliana Zuliana (Proceeding International Seminar of Islamic Studies, 2021)
This research focuses on the development of preeminent Islamic school in Indonesia which are now growing rapidly. This study using the literature review method resulted in a conclusion that now public schools already have Islamic labels and uniqueness. Although this school is a public school (not a Madrasah), the addition of an Islamic label behind it makes this school a preeminent Islamic school. The factors behind the growth of preeminent Islamic school in Indonesia include; 1) Education and Religion of the Majority in Indonesia, 2) Education and Morality (moral needs), 3) Education and Religious Quality, Political, Sociological and Economic Development of Indonesian Muslims.Keywords: Development, Preeminent, Islamic School